Fabric Flammability Changes Due to Hair Spray Exposure (Journal of Fiber Bioengineering and Informatics, 2024)
Hairspray is widely used worldwide in beauty salons and barbershops to create customized hairstyles.However, the chemicals in hairspray are highly flammable, posing significant risks of burn injuries to staffand customers, especially when clothing is exposed to heated tools such as hairdryers or curling irons.Hairsprays typically contain polymer-based adhesives, liquid solvents, and propellant gases. Duringapplication, a notable amount of overspray can settle on clothing, depositing a thin adhesive layer onthe fabric. This research project aimed to assess how exposure to hairspray alters the flammabilityof different fabric types, including Silk, Cotton, Wool, Nylon, and Polyester. Fifteen fabric sampleswere treated with hairspray, while another fifteen samples served as untreated controls. All treatedsamples were exposed to the same amount of hairspray and left to dry for 24 hours, while the controlsamples remained untouched. Flame temperatures and total burn times were measured during testing.The findings revealed that the maximum flame temperatures for Polyester increased by 140%, withburn times rising by 74%. For Nylon, flame temperatures rose 178%, and burn times increased 75%.In contrast, the flame temperatures and burn times for Silk, Cotton, and Wool remained unchanged.The results of further analysis using differential scanning calorimetry and Raman Microspectroscopysuggested that the flammability differences between natural and synthetic fibres are linked to fibrepolarity and hydrophobicity variations.